POSITIVE INTERDEPENDENCE AND PROMOTIVE INTERACTION IN ONLINE COOPERATIVE LEARNING TO SUPPORT WRITING ACHIEVEMENT - Nurvianti, Sussi; Riyanti, Dwi; Sada, Clarry (Education Administration Study Program, School of Postgraduate Studies, Universitas Riau, 2024)
This study aimed to get a clear description of how positive interdependence and promotive interaction as two of five key elements in cooperative learning account for the success of students’ achievement in essay writing. A mixed method design was employed to describe if the characteristics of both positive interdependence and promotive interaction were found in the activities performed by the groups and whether these two elements had the potential to support students’ achievement in essay writing. Using Google Classroom as the learning management system to mediate the learning process, there were 52 undergraduate students participated in this study who were divided into 10 small groups consisting of 5-6 students. Data required for this study was collected from both written records of students’ activities in online discussions and the scores achieved by the groups on each task. The findings showed an interesting fact that the characteristics of both of the elements were easily found in all parts of the activities performed by all groups in the online discussions. However, the average scores of their works indicated that there was not any meaningful improvement from the first to the last activities. The result implied that although cooperative learning is possible to be applied in an online classroom setting, it needs proper preparation and well-designed writing tasks to make it possible to support students’ writing achievement.